PRYWATYZACJA I DEREGULACJA W SFERZE INFRASTRUKTURY - Ratajczak, Marek (Wydział Prawa i Administracji UAM, 2000)
The Author is occupied with motivations and possibilities of changes concerning functioning of infra-structural components of national economy. He stresses the need for non ideological approach to privatisation problems; in case of infra-structural links of the economy the choice consists not in opposing a good market to a „bad State” but it is often reduced to declare itself for a deceptive market, anyway, or for equally deceptive State. When making a choice between less or more market solutions one can not make no mention of extra-economic circumstances or of premises of social order. Next the Author states that all postulates relating to privatisation and deregulation affect mainly the sphere of exploitation of the infrastructure and to a less extent - the infrastructure itself. For instance, the idea, otherwise proper, of deregulation of the transportation is not to be automatically identified with a postulate to abandon public regulation of developing the transportation infrastructure. So, a deregulation of infra-structural components of the economy does mean to a great measure a transition to other form of regulation; it is important on this opportunity to separate the States’ role as a regulator from possible assuming by this State of a role of the owner. Finally, the Author indicates a necessity of distinguishing a regulation aimed at establishing who and what are supposed to be done (the so-called structural regulation resolving itself into a reglamentation) from a regulation which aims at shaping the functioning of firms (the so-called regulation of the behaviour). The first one should be restricted to a maximum whereas the second one - consolidated and developed.
PRIVATISATION AND DEREGULATION IN THE SPHERE OF INFRASTRUCTURE